Thermodynamic performance analysis of an improved coal-fired power generation system coupled with geothermal energy based on organic Rankine cycle. (December 2022) - Zhang, Hongsheng; Hao, Ruijun; Liu, Xingang; Zhang, Ning; Guo, Wenli; Zhang, Zhenghui; Liu, Chengjun; Liu, Yifeng; Duan, Chenghong; Qin, Jiyun
Abstract: A new improved coal-fired power generation system coupled with geothermal energy (GEACPG) based on organic Rankine cycle (ORC) is put forward to enhance power generation capacity of medium-low temperature steam of steam turbine (ST) and medium-low temperature geothermal energy. Besides, with ORC as the bottom cycle, the new integrated method can also prevent air-cooled condenser from freezing in winter. The medium-low temperature geothermal energy and exhaust steam of ST are employed to preheat ORC, and some medium-temperature steam that has expanded to a certain extent in the ST is extracted to drive ORC in the GEACPG. The thermodynamic performances of the following three systems, namely original coal-fired power generation system (CPG), coal-fired power generation system with exhausted steam and extraction steam as heat sources of ORC (CPGEE) and GEACPG, taking a 600 MW direct air-cooled unit as a case study, are analyzed and compared according to the first and second laws of thermodynamics. It is found that the thermodynamic performance of the whole system can be improved by using some medium-temperature steam from ST to drive ORC with the exhausted steam as preheating heat source. The thermodynamic performance can be further improved by introducing geothermal energy. Compared with CPG, the overall generated power is increased by 22.61 MW, the overall exergy and thermal efficiencies are enhanced by 1.07% and 1.55% as the extracted steam flow rate is 150 kg/s at 100%THA in the GEACPG. In addition, the generated power of geothermal energy is increased by 1, 272 kW, the power generation exergy and thermal efficiencies of geothermal energy are enhanced by 29.1% and 6.0% at 70 °C geothermal temperature. The new solution can not only enhance the whole system thermodynamic property but also significantly enhance generation power capacity of the medium-low temperature geothermal energy.